Uganda : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver of Performance Criterion, and Extension of Arrangement; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uganda. (IMF Staff Country Reports; Country Report, 2005)
This paper focuses on Uganda's Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF), Request for Waiver of Performance Criterion, and Extension of Arrangement. Performance relative to the program performance criteria and benchmarks has generally been satisfactory. All quantitative performance criteria for December 2004, with the exception of that on the accumulation of domestic arrears, were observed. The structural performance criterion and two of the four benchmarks through March 2005 were also met.